A General and Highly Selective Cobalt‐Catalyzed Hydrogenation of N‐Heteroarenes under Mild Reaction Conditions. Issue 12 (14th February 2017) - Adam, Rosa; Cabrero‐Antonino, Jose R.; Spannenberg, Anke; Junge, Kathrin; Jackstell, Ralf; Beller, Matthias
Abstract: Herein, a general and efficient method for the homogeneous cobalt‐catalyzed hydrogenation of N‐heterocycles, under mild reaction conditions, is reported. Key to success is the use of the tetradentate ligand tris(2‐(diphenylphosphino)phenyl)phosphine). This non‐noble metal catalyst system allows the selective hydrogenation of heteroarenes in the presence of a broad range of other sensitive reducible groups. Abstract : Reduction ! Quinolines and related N‐heteroarenes are hydrogenated using [Co]/L . The reactions proceed under mild conditions in a highly selective manner.